(3agQSJ GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s
(3ChdgG (B:s
(3GdMeO ddg hdj GdMeO heSJMbg(B... (3CeG HYO, aEf deG QCjJ LeGYI ef TjhN WGFaJfG ef CUMGH GdMOjK(B...s
(3BNQgG (B:s
(3fhGOQ CNHQfG HgG LeGYI Yf CHj GdeaVd Yf MejO Yf GHf YUGe(B. (3Je agQSJ GdTjN GdWhSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B72s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B225s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs